Gender’s Role in Shaping Empathy and Psychological Well-Being: Insights from Management Students - A. K , Sreedisha; Celina , A. (Journal of Ecohumanism, 2025)
In the context of management education, empathy and psychological wellbeing are particularly crucial since they have a big impact on how individuals live their personal and professional lives. The purpose of this study is to examine the variables that influence management students’ psychological wellbeing and capacity for empathy and the association between empathy and psychological wellbeing. This study involved 200 management students from Chennai, India and the management courses considered for study are Master of Business Administration and Bachelor of Business Administration. The study uses a quantitative research methodology to get information from a sample of management students. Regression analysis , correlation, and structural equation modelling are used in data analysis to find the predictive characteristics and their connections to empathy and psychological wellbeing. The results of this study have consequences for management education institutions, counselling services, and policymakers. Educational institutions can create focused programs to promote empathy and psychological wellbeing in management students by identifying the variables that have a beneficial impact on these traits. Future managers may benefit in terms of their own wellbeing, interpersonal effectiveness, and leadership skills as a result. This study contributes to the body of knowledge regarding empathy and psychological wellbeing in management students and offers helpful knowledge for professionals, educators, and scholars in the field.